How capital structure affects business performance in Chinese listed commercial banks - Luo, Ting (2011)
In the end of 2006, China realized the opening of financial market, thus Chinese commercial banks have to face the global competitors. The business performance of banks is the overall reflection of competence; however, the performance of Chinese banking industry is still weaker. According to some theoretical basis of capital structure, capital structure affects overall business performance by influencing the corporate governance of corporations. The capital structure of commercial banks also plays a vital role in achieving the financial goals and moderate operation. Thus this study aims to research how commercial banks’ capital structure affects business performance in China, and gives the recommendation to optimize the banks’ capital structure and improve business performance.